Analyzing the Level of CSR Practices in Relation to Customer Satisfaction in the Context of Banking Industry in Bangladesh - Hossain, Md. Sumon; Rayhan, Md. Johir; Uddin, Maeen; Rahman, S.M. Masudur (International Journal of Economics and Financial Issues, 2023)
This study aims to show the degree of Corporate Social Responsibility (CSR) practices and satisfaction of customer that are related while determining the relationship (Significant or Insignificant) between these two in the context of banking industry in Bangladesh. Authors adopt simple random sampling and collects data from 335 customers of ten listed banking companies through a survey questionnaire. The data have been analyzed through employing various statistical tests such as Skewness, kurtosis, cook distance, variance inflation factor (VIF), Durbin-Watson statistics and simple regression analysis. According to the authors' analysis of the composite Index, the teacher's mean customer satisfaction (CS) index and mean CSR practice index are both at their highest levels. The relationship measured by composite index between CSR practice and customer satisfaction that is found strongly positive and significant, indicated by empirical findings. The finding implies that if CSR initiatives increase, customer satisfaction levels will rise as a result. The authors have deduced from the literature that there isn't any evidence of an investigation that looks at the relationship between CSR practices and customer satisfaction among Bangladeshi companies; hence, there is a contribution to new knowledge as the analysis produces new insights in the context of a developing economy.